A simple synthesis method to prepare a molybdenum oxide hole-transporting layer for efficient polymer solar cells. Issue 13 (23rd January 2017) - Li, Yanping; Yu, Huangzhong; Huang, Xinxin; Wu, Zuping; Chen, Mingdong
Abstract : We report a simple synthetic method to prepare amorphous molybdenum oxide (p-MoO3 ) using a favorably stable peroxomolybdic acid organosol as the precursor solution prepared by an ultrasonic reaction for the first time. Abstract : We report a simple synthetic method to prepare amorphous molybdenum oxide (p-MoO3 ) using a favorably stable peroxomolybdic acid organosol as the precursor solution prepared by an ultrasonic reaction for the first time. The favorably smooth and dense surface morphology of the p-MoO3 layers are obtained under 150 °C thermal treatment with good optical properties and a high work function ( W F ) of 5.26 eV. During the annealing treatment two different oxidation states of Mo ions are observed with increasing the annealing temperature to 150 °C and 200 °C. The best performance of the P3HT:PC71 BM devices with p-MoO3 anode buffer layers has been achieved under 150 °C treatment with a power conversion efficiency (PCE) of 4.02%, a V OC of 0.59 V, a J SC of 10.70 mA cm −2, and a FF of 63.7%, superior to the corresponding PEDOT:PSS modified devices. Furthermore, the performance of the PTB7:PC71 BM devices with the annealed p-MoO3 buffer layers has also been dramatically improved with the best performance parameters of a PCE of 8.46%, a V OC of 0.73, a J SC of 17.02 mA cm −2, a FF of 68.1% for 150 °C. The improved performance of the devices originates from the following factors; (i) the favorable and compact surface morphology of the annealed p-MoO3 films leading to a higher rectification ratio and lower leakage current. (ii) The formation of oxygen vacancies and the growing Mo 5+ cation leading to the change of W F under the annealing treatment. The highest W F of 5.26 eV for 150 °C treatment influences the built-in electric field of the devices with the photocurrent being extracted efficiently at a short-circuit.